Multi-view horizon-driven sea plane estimation for stereo wave imaging on moving vessels. (October 2016) - Bergamasco, Filippo; Benetazzo, Alvise; Barbariol, Francesco; Carniel, Sandro; Sclavo, Mauro
Abstract: In the last few years we faced an increased popularity of stereo imaging as an effective tool to investigate wind sea waves at short and medium scales. Given the advances of computer vision techniques, the recovery of a scattered point-cloud from a sea surface area is nowadays a well consolidated technique producing excellent results both in terms of wave data resolution and accuracy. Nevertheless, almost all the subsequent analyses tasks, from the recovery of directional wave spectra to the estimation of significant wave height, are bound to two limiting conditions. First, wave data are required to be aligned to the mean sea plane. Second, a uniform distribution of 3D point samples is assumed. Since the stereo-camera rig is placed tilted with respect to the sea surface, perspective distortion do not allow these conditions to be met. Errors due to this problem are even more challenging if the optical instrumentation is mounted on a moving vessel, so that the mean sea plane cannot be simply obtained by averaging data from multiple subsequent frames. We address the first problem with two main contributions. First, we propose a novel horizon estimation technique to recover the attitude of a moving stereo rig with respect to the sea plane. Second, an effective weighting scheme is described to account for the non-uniform sampling of the scattered data in the estimation of the sea-plane distance. The interplay of the two allows us to provide a precise point cloud alignment without any external positioning sensor or rig viewpoint pre-calibration. The advantages of the proposed technique are evaluated throughout an experimental section spanning both synthetic and real-world scenarios. Abstract : Highlights: We propose an optical horizon estimation technique to recover the attitude of a moving stereo rig with respect to the sea plane. Projective distortion is corrected to account for the non-uniform distribution of the reconstructed point cloud. The alignment of each sea surface is improved without using external positioning sensors.